Horay's Personalized Learning System Of Instruction And Course Review On Students' Concept Understanding Ability And Activeness - Nawati, Cipra; Yahfizham; Afri, Lisa Dwi (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This study aims to determine the Influence of The Personalized System Of Instruction Learning Model And Horay Course Review On The Ability To Understand Concepts And Activeness Of Class X Students Of Private High School Harapan Mekar Medan Learning Year 2021-2022. This research methodology uses quantitative research methods. The research population is all students of class X of Sma Swasta Harapan Mekar Medan with a total of 28 students in experimental class 1, namely class X-A and 27 students in experimental class 2, namely class X-B. The sampling method is non-probability sampling with a saturated sampling technique where the researcher will take all members of the population to be sampled. Data analysis was carried out with a t-test, with the following results: 1) There is an influence of PSI on concept understanding ability 2) There is an influence of PSI on student activity 3) There is an influence of CRH on students' concept understanding ability 4) There is an influence of CRH on student activity 5) There is no difference in the ability to understand concepts taught with PSI and CRH 6) There is no difference in activeness taught with PSI and CRH.